2021
DOI: 10.3390/v13112305
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Leishmania-LRV Co-Phylogenetic Patterns and Evolutionary Variability of Viral Proteins

Abstract: Leishmania spp. are important pathogens causing a vector-borne disease with a broad range of clinical manifestations from self-healing ulcers to the life-threatening visceral forms. Presence of Leishmania RNA virus (LRV) confers survival advantage to these parasites by suppressing anti-leishmanial immunity in the vertebrate host. The two viral species, LRV1 and LRV2 infect species of the subgenera Viannia and Leishmania, respectively. In this work we investigated co-phylogenetic patterns of leishmaniae and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 73 publications
1
25
0
Order By: Relevance
“…We used two LRV-positive Leishmania spp. ( L. guyanensis M4147 and L. major T44g) and overexpressed capsids of their own viruses (LRV1-4 and LRV2, respectively) as well as those of phylogenetically distant LRV1s from L. guyanensis Lg 2014 and L. braziliensis LEM2700 ( 21 ). Successful integration and capsid expression were confirmed by RT-qPCR and Western blotting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used two LRV-positive Leishmania spp. ( L. guyanensis M4147 and L. major T44g) and overexpressed capsids of their own viruses (LRV1-4 and LRV2, respectively) as well as those of phylogenetically distant LRV1s from L. guyanensis Lg 2014 and L. braziliensis LEM2700 ( 21 ). Successful integration and capsid expression were confirmed by RT-qPCR and Western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…The first approach is based on the disruption of the ideal 120:2 ratio between the capsid and fused (capsid-RDRP) protein, which results in a decreasing proportion of correctly assembled virions and subsequent viral loss ( 31 , 41 ). We also tested two C-terminally truncated versions that preserved all functional capsid elements ( 21 , 42 ), because it was demonstrated virus loss can be observed even with an abridged capsid protein in the case of the related L-A virus of yeasts ( 35 ). The results in the L. guyanensis- LRV1 system led to complete viral elimination, regardless of the experimental construct used, suggesting the C-terminal part of the capsid protein is not necessary for the assembly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LRV1 has been found in New World species such as Lgy (Tarr et al, 1988) and Lbr (Zangger et al, 2013), while another species of LRV, termed LRV2 has been found in Old World L. major (Scheffter et al, 1994), L. aethiopica (Zangger et al, 2014) and L. infantum (Hajjaran et al, 2016). The difference between LRV1 and LRV2 lies within the genetic organization and replication mechanisms (Lee et al, 1996;Se et al, 2005;Fujimura and Esteban, 2011;Kostygov et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Other groups of RNA viruses infecting trypanosomatids are bunyaviruses and narnaviruses, along with some viruses of more restricted distribution [48]. The applied methodological approaches include whole-genome and whole-transcriptome sequencing followed by the phylogenomic analyses of viruses and their respective trypanosomatid hosts [49].…”
mentioning
confidence: 99%